The Effect of Lemon Aromatherapy Inhalation on Pain Scale Reduction in Patients after Lower Extremity Fracture Surgery - Rahmi, Upik; Fitriana, Lisna Anisa; Anggraeni, Syifa Fadhilah (Jurnal Pendidikan Keperawatan Indonesia, 2025)
Introduction: Fractures are disruptions in the continuity of bone structure that may involve nerve injury, leading to postoperative pain and discomfort. Postoperative pain is a common and inevitable condition that requires effective management to prevent complications and enhance patient comfort. In addition to pharmacological therapy, non-pharmacological interventions such as aromatherapy are increasingly used as complementary approaches in pain management. Lemon aromatherapy is believed to have analgesic and relaxing properties that can help reduce pain perception after surgery. Objective: This study aimed to examine the effectiveness of lemon aromatherapy inhalation in reducing pain intensity among patients following lower extremity fracture surgery. Methods: A quasi-experimental study with a two-group pretest–posttest design was conducted at a hospital. A total of 20 postoperative patients with lower extremity fractures were recruited using a total sampling technique. The intervention involved inhalation of lemon aromatherapy by applying 5–6 drops of lemon essential oil onto a tissue placed on the patient’s chest for 30 minutes, accompanied by deep breathing exercises. Pain intensity was measured using the Numeric Rating Scale (NRS). Data analysis included tests of normality and homogeneity, paired sample t-tests, independent sample t-tests, and n-gain analysis. Results: The results showed a significant reduction in pain intensity after the intervention (p = 0.000). The mean pain score decreased from 7.9 (severe pain) before the intervention to 4.6 (mild pain) after the intervention, indicating a clinically meaningful improvement. Conclusion: Lemon aromatherapy inhalation is effective in reducing postoperative pain intensity among patients after lower extremity fracture surgery and may be considered a complementary nursing intervention for postoperative pain management.